Empowerment of Organic Fertilizer Farmer Groups in Developing Green House-Based Organic Vegetables - Asyhari Asyhari; Budhi Cahyono; Siti Sumiati; Dyana Wijayanti; Naila Najihah; Choiril Anwar (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
Organic vegetables produced by the women farmers group and organic fertilizers produced by the youth groups are not yet productive. The purpose of this community service activity is to empower the women farmers groups and the youth group in the village of Manggihan, Getasan District, Semarang Regency so that they can improve the quality of organic vegetable and organic fertilizers products. This community service is carried out by using ABCD approach, which is an approach to understanding and internalizing assets, potential, strength, and utilization independently and optimally. The results of this community service activity concluded that the entrepreneurial mindset of organic vegetable and organic fertilizer farmer groups was more creative and innovative in processing Green House-based organic vegetables, skilled in bookkeeping, online marketing, and making Intellectual Property Rights to increase awareness of healthy living, increase profits, business, and welfare of rural communities